Progranulin protects against the tissue damage of acute ischaemic stroke. (16th June 2015) - Zhao, Chunyu; Bateman, Andrew
Abstract : This scientific commentary refers to 'Multiple therapeutic effects of progranulin on experimental acute ischaemic stroke', by Kanazawa et al. (doi:10.1093/brain/awv079 ).